Processing of mycotoxin contaminated waste streams through anaerobic digestion. (January 2018) - De Gelder, L.; Audenaert, K.; Willems, B.; Schelfhout, K.; De Saeger, S.; De Boevre, M.
Graphical abstract: Highlights: Mycotoxins do not affect methane production during anaerobic digestion. Mycotoxins are being readily degraded under pilot scale conditions. Mycotoxin degradation is more complete under thermophilic conditions. Abstract: Food and feed stocks heavily contaminated with mycotoxins are rendered unfit for consumption and therefore discarded as waste. Due to the lack of guidelines and in accordance with the prudent avoidance principle, these waste streams are often incinerated. For better valorization, these streams could be used as input for anaerobic digestion. However, the degradation of multiple mycotoxins during anaerobic digestion and their effect on the methane production is currently unknown. In batch tests spiked with mycotoxins, aflatoxin B1, ochratoxin A, deoxynivalenol, zearalenone and T-2 toxin were degraded for more than 90%. For mesophile and thermophile digestion respectively, fumonisin B1 was degraded for 70% and 85%, and most ergot alkaloids for 64% and 98%. Neither biogas production, nor methane production were influenced by the presence of the mycotoxins. Subsequently, semi-continuous reactors fed with contaminated maize resulted in more than 99% degradation for all mycotoxins after 1.8 hydraulic retention time with stable biogas production and process parameters. This study shows that mycotoxin contaminated organic waste can be safely valorized to methane while the digestate is void of mycotoxin residues.